Research on Crisis Management Practices in the Travel Industry during the Epidemic - Chen, Kao-Shan; Chen, Yi-Hung (International Journal of Scientific Research and Management (IJSRM), 2022)
The main purpose of this paper is to study the impact of travel agencies' crisis management practices on willingness of employee retention and business operations during the COVID-19 outbreak. The results of the study found that there are significant differences in the different statistical variables on crisis management practice and the effect of crisis management practice. Secondly, crisis management practices have a positive impact on employees' willingness to stay. Third, crisis management practices have a positive impact on business operations. Fourth, the talent management, labor force and cost control included in the crisis management practice have a positive impact on willingness of employee retention and business operation.